Imagine the possibilities: information without overload - Jago, Mark (2006)
Information is often modelled as a set of relevant possibilities, treated as logically possible worlds. However, this has the unintuitive consequence that the logical consequences of an agent's information cannot be informative for that agent. There are many scenarios in which such consequences are clearly informative for the agent in question. Attempts to weaken the logic underlying each possible world are misguided. Instead, I provide a genuinely psychological notion of epistemic possibility and show how it can be captured in a formal model, which I call a fan. I then show how to use fans to build formal models of being informed, as well as knowledge, belief and information update.